Comparative Study of the MUI Fatwa and Sadd Al-Żarī'ah Concerning Spirit Dolls - Bayu Prasetyo; Dewi Ayu (Postgraduate Programme of UIN Kiai Haji Achmad Siddiq Jember, 2022)
This research investigates the phenomenon of spirit dolls in the context of Islamic law and the principles of Sadd Al-Żarī'ah, with a focus on the response of the Indonesian Ulema Council (MUI) to the practice. This study uses descriptive qualitative methods, collecting data through interviews with ulama, MUI members, and community surveys, as well as analysis of documents related to MUI fatwas. The results show that the MUI classifies belief in dolls that have spirits as shirk, contrary to tawhid. The Sadd Al-Żarī'ah principle is applied to prevent damage to morals and beliefs, through an educational and preventive approach. This research also highlights the role of the media in popularizing the spirit doll phenomenon, as well as the psychological and social impact of this belief. Recommendations include increased public education, collaboration between religious institutions and the media, and more research into the psychological impact of belief in spirit dolls.